2012
DOI: 10.1073/pnas.1118174109
|View full text |Cite
|
Sign up to set email alerts
|

Natural and sexual selection in a monogamous historical human population

Abstract: Whether and how human populations exposed to the agricultural revolution are still affected by Darwinian selection remains controversial among social scientists, biologists, and the general public. Although methods of studying selection in natural populations are well established, our understanding of selection in humans has been limited by the availability of suitable datasets. Here, we present a study comparing the maximum strengths of natural and sexual selection in humans that includes the effects of sex a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
93
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(105 citation statements)
references
References 43 publications
10
93
2
Order By: Relevance
“…They measured variation by the standardized variance (Crow's I;Crow (1958)), which measures the maximum opportunity for selection. Courtiol et al (2012) found a value close to 2, which is much higher than the values (≈ 0.5) that we calculate for the countries in our dataset during the transition (Figure 9). Of course, the vital rates in Finland in the 18th and 19th century are different from those of Europe during the second demographic transition, but this crude comparison suggests that the opportunity for selection is to a large part determined by heterogeneity, with only a relatively small contribution from individual stochasticity.…”
Section: Individual Stochasticitycontrasting
confidence: 45%
See 1 more Smart Citation
“…They measured variation by the standardized variance (Crow's I;Crow (1958)), which measures the maximum opportunity for selection. Courtiol et al (2012) found a value close to 2, which is much higher than the values (≈ 0.5) that we calculate for the countries in our dataset during the transition (Figure 9). Of course, the vital rates in Finland in the 18th and 19th century are different from those of Europe during the second demographic transition, but this crude comparison suggests that the opportunity for selection is to a large part determined by heterogeneity, with only a relatively small contribution from individual stochasticity.…”
Section: Individual Stochasticitycontrasting
confidence: 45%
“…This measured variance includes both individual stochasticity and heterogeneity, but such studies are rare, and many of them (e.g., Spuhler 1976) consider only surviving women and/or only married women (Courtiol et al 2012). In one exceptional study, however, Courtiol et al (2012) measured the standardized variance in LRO for an entire cohort of Finnish women living in the period 1760-1849, using data from the church books of four Finnish populations. They measured variation by the standardized variance (Crow's I;Crow (1958)), which measures the maximum opportunity for selection.…”
Section: Individual Stochasticitymentioning
confidence: 99%
“…Since the eighteenth century in Finland, the Lutheran Church has required the submission of accurate registers of all births, inter-parish movements, marriages and deaths in the country. From these records, we compiled life histories for individuals from rural parishes previously used in analyses of life-history traits (see the electronic supplementary material for more details) [15].…”
Section: Materials and Methods (A) Variables And Datamentioning
confidence: 99%
“…Finnish women living 1760--1849 had an average of 4.27 babies, whereas landowning women had an average of 4.55 babies: a change in absolute fitness of this magnitude would cause a geometric rise in the number of descendants in a few generations [14] (Figure 2a). …”
Section: Selection and Pregnancymentioning
confidence: 99%